1999
DOI: 10.1177/00220345990780070801
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Clenching Intensity on Bite Force Balance, Occlusal Contact Area, and Average Bite Pressure

Abstract: It has been difficult for investigators to simultaneously and reliably evaluate bite force in the intercuspal position with the area and location of occlusal contacts. This study was designed to investigate the variations in these parameters with respect to two factors: three levels of clenching and the preferred chewing side. Human subjects with normal occlusion were examined with a recently developed system (Dental Prescale Occluzer, Fuji Film, Tokyo, Japan). The three levels of clenching intensity were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
250
0
14

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(278 citation statements)
references
References 34 publications
14
250
0
14
Order By: Relevance
“…(7)). Since fracture load before and after the applied artificial aging procedure represents the most relevant factor for predicting mechanical reliability, it should be considered the primary outcome and comprise a "safety buffer" of at least 50% as when compared to maximum in vivo loading forces on implants or teeth (maximum voluntary contraction or greatest clenching strength measured in clinical trials was reported to be in the range of 350-400 N in the molar region [41][42][43]). This results in a required fracture load of at least 600 N. For "standard" pre-clinical evaluation of mechanical long-term reliability (as it should be mandatorily required), phase transformation measurements might be considered supplementary for fault tracing or when comparing different materials or processing technologies.…”
Section: Suitability Of the Experimental Setup For Lifetime Estimatiomentioning
confidence: 99%
“…(7)). Since fracture load before and after the applied artificial aging procedure represents the most relevant factor for predicting mechanical reliability, it should be considered the primary outcome and comprise a "safety buffer" of at least 50% as when compared to maximum in vivo loading forces on implants or teeth (maximum voluntary contraction or greatest clenching strength measured in clinical trials was reported to be in the range of 350-400 N in the molar region [41][42][43]). This results in a required fracture load of at least 600 N. For "standard" pre-clinical evaluation of mechanical long-term reliability (as it should be mandatorily required), phase transformation measurements might be considered supplementary for fault tracing or when comparing different materials or processing technologies.…”
Section: Suitability Of the Experimental Setup For Lifetime Estimatiomentioning
confidence: 99%
“…7-11 Contact information from these systems is limited because their sensors could interfere with and alter occlusion, contacts are not directly related to occlusal anatomy, and the results are two-dimensional. 12,13 Addition silicones are frequently used to record contacts because of their low viscosity, accuracy, and stability. The flow properties and uniform distribution of the materials across occlusal surfaces of teeth ensure minimal interference on closure.…”
Section: Introductionmentioning
confidence: 99%
“…This system is now being used in various fields of dental research, particularly by Japanese researchers [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][22][23][24][25][26][27][28][29][30][31][32][33] . These studies have suggested that this system might help evaluating masticatory function and could be applicable to general dental clinical work.…”
Section: Introductionmentioning
confidence: 99%